Aceh Besar 7 لترقية قدرة الطلبة على فهم تركيب الجمل المفيدة بالمدرسة المتوسطة Power Point تطبيق طريقة المعدلة بوسيلة - Dhifa, Maisuratud; Qusaiyen, Qusaiyen; Ninoersy, Tarmizi (Fakultas Tarbiyah dan keguruan- UIN Ar-Raniry, 2020)
In this study, the researcher observed thatteachersin MTsN 7 Aceh Besar do not use a special method andinterestingmeans in teaching Arabic, but rather fixate on the memorization of textsand listen to the students’ memorization in class. Therefore, students find it difficult to learn Arabic and eventually find the lesson a burden. They can not express their ideas directly and end up with losing interest in the study. They lack enthusiasm and have no strong motivation to enrich and apply the vocabulary and express their knowledge of Arabic. One of the reasons for this problem is that teachers do not use an attractive tool during the learning process. As an effort to overcome these problems, the researcher uses the Snowball Throwing method to improve students' understanding, especially on the lesson about grammer. The purpose of this study is to identify the influence and response of students of MTsN 7 in learning the lesson about Grammer by using Mu’addalah method. The research method used by the researcher is pre-experiment with pre-test and post-test design in one group design, and to collect the data,the researcher uses questionnaire and test. The approach used by the researcher is quantitative. As the population of this study are all students in MTsN 7, students in the second grade are selected as the sample, which is amounted to 28 students. The result is obtained from T-test Sig (.05<.001). This shows that the hypothesis is zero (ho) is rejected and hypothesis (Ha) is accepted, it is evident that the usage of Mu’addalah method is influential to improve student’s understanding about Grammer lesson.